TOPICS OF MEDIA LITERACY IN THE CONTENT OF PRIMARY AND SECONDARY EDUCATION IN THE SUBJECT OF THE LATVIAN LANGUAGE - Murinska, Sandra; Kaļva-Miņina, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
People are facing the growth and access of information, as well as the various forms of communication. While some part of society experience a lack of information, others are flooded with printed, broadcast and digital content. UNESCO argues that media and information literacy can provide answers to questions related to our culture of information and critical thinking. Media literacy must be discussed through education, because teachers are the key person to literacy of the society. An important way to update media literacy among teachers and students is to introduce it in the curriculum. The topic of media literacy is currently included in the curriculum based on the new competency approach in Latvia. When evaluating the curriculum of the subject of the Latvian language, the aim of the paper is to determine which topics and aspects of media literacy are included in the curriculum of the Latvian language and what pupils' skills and knowledge they promote.